Pro SharePoint with jQuery - Duffy, Phill (Apress, 2012)
Pro SharePoint with jQuery is all about how to work seamlessly with the two popular technologies to create rich and interactive web parts, application pages, and more. In this book, author Phill Duffy provides complete, meaningful and realistic examples to really help you understand the key concepts and their integration points. Inside, you'll find all the tools and resources you need to use jQuery to provide the next level of SharePoint functionality. Learn what it takes to get ready to use jQuery, how to create rich, responsive, and highly functional user interfaces, how to call the SharePoint web services and work with HTML elements, and much more with Pro SharePoint with jQuery.  Takes you through the different ways of integrating jQuery into your SharePoint environment Provides various levels of projects to show off the extensive capabilities of jQuery within SharePoint Teaches you how to provide rich, fluent and interactive jQuery-enabled user interfaces